A METHOD FOR CALCULATING THE SLOPE ERROR OF MIRRORED SURFACES CONSISTED OF FACETS CURVED IN ONE AXIS USED IN CONCENTRATED SOLAR POWER (CSP) TOWER SYSTEMS - Göttsche, Joachim; Lampkowski, Marcelo; Bezerra, Pedro Henrique Silva; Teramoto, Érico Tadao; Boura, Cristiano Teixeira (ENERGIA NA AGRICULTURA, 2017)
Heliostats are considered the most important cost elements of a Concentrated Solar Power (CSP) power tower system and the use of suitable heliostats can generate reductions up to 40% in the power losses. Therefore, the design and optimization of heliostats have a great importance in solar tower power plant projects. This technical brief aims to present a method for calculating the slope error of bended-mirrored surfaces used in CSP power tower systems. For that, a heliostat composed by six mirror facets measuring 2.5 meters (width) x 0.533 meters (height) each, curved only in one axis and with a 30 meters’ focal length was considered. The found slope errors results using the numerical approach and the analytical approach were very similar, suggesting that both methods are applicable in this case.